2005
DOI: 10.1093/jjco/hyi182
|View full text |Cite
|
Sign up to set email alerts
|

Is there any Role for Sentinel Node Mapping in Colorectal Cancer Staging? Personal Experience and Review of the Literature

Abstract: SN mapping is an easy and cost-effective technique that holds promise and warrants further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
1
19
0
2
Order By: Relevance
“…In this study, a detection rate of SLN of 90% was achieved, although the number of cases ( n = 33) was relatively low. Some authors postulate a minimal learning curve of 10 cases per surgeon to become familiar with SLNM [5,10–14]. Thus, Saha et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a detection rate of SLN of 90% was achieved, although the number of cases ( n = 33) was relatively low. Some authors postulate a minimal learning curve of 10 cases per surgeon to become familiar with SLNM [5,10–14]. Thus, Saha et al.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated tumor cells are defined as either single tumor cells or as clusters of tumor cells of 0.2 mm or less 60, 61. Increase detection of such tumor deposits in lymph nodes in many solid cancers including colorectal cancer 62–65 has been made possible by SLN mapping technique. Although numerous studies have concluded that micrometastasis in SLNs is associated with adverse outcome compared to node‐negative disease, others failed to show such a correlation.…”
Section: Sln Micrometastasis and Clinical Outcome In Colorectal Cancermentioning
confidence: 99%
“…This definition has been extended in the AJCC 7th edition to include non-cohesive infiltrate of >200 cells as micrometastasis. Sentinel lymph node mapping has been evaluated as a technique to enhance the detection rates of micrometastasis in many solid tumors including colorectal cancer [7][8][9][10]. Since the first feasibility study in 1997 [7], many single and multi-center studies [8][9][10] have demonstrated high success rates, sensitivity and accuracy of this procedure.…”
Section: Detection Of Micrometastasis In Colorectal Cancermentioning
confidence: 99%